2022
DOI: 10.1186/s12888-022-03790-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-traumatic stress disorder symptoms among patients with mental disorder during the COVID-19 pandemic

Abstract: Background The outbreak of the COVID-19 pandemic has caused extensive public health concerns, posing significant challenges to healthcare services. One particular area of concern is the mental health of patients with mental disorder, who are often a neglected group. The aim of this study was to investigate the prevalence of, and associated factors for symptoms of post-traumatic stress disorder (PTSD) among patients with mental disorder in China during the COVID-19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It has been observed that old people present a lower level of acute stress during stressful events than young people (Reynolds et al, 2016). In the COVID-19 context, the patron is the same (Cai et al, 2020;Tang et al, 2022). On the other hand, anxiety and depressive symptoms are also most common in young people (Gambin et al, 2021;Solomou and Constantinidou, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that old people present a lower level of acute stress during stressful events than young people (Reynolds et al, 2016). In the COVID-19 context, the patron is the same (Cai et al, 2020;Tang et al, 2022). On the other hand, anxiety and depressive symptoms are also most common in young people (Gambin et al, 2021;Solomou and Constantinidou, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, anxiety and depressive symptoms are also most common in young people (Gambin et al, 2021;Solomou and Constantinidou, 2020). Age, along with other factors such as being female, and the severity of COVID-19 symptoms have been identified as risk factors for the development of PTSD, anxiety, depression, or other mental comorbidities , Nie et al, 2020, Ochnik et al, 2022Tang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Still, the prevalence of these two kinds of posttraumatic stress disorder is similar in the world, both about 20%.In a study in China, Beijing learned about people's mental health by distributing questionnaires to patients in four psychiatric hospitals. The results showed 41.3% of patients have post-traumatic stress disorder [20].…”
Section: Post-traumatic Stress Disordermentioning
confidence: 98%
“…11,12 PTSD is a stressrelated psychological condition that occurs immediately following traumatic experience, such as severe accident, near-death experience, and sexual or physical violence. 13 This occurs when the memories, emotions, or thoughts experienced during the trauma or event reoccur, leading to restrictions and inconvenience in the individual's day-to-day life. 13 Overall, the prevalence of PTSD among individuals who have recovered from COVID-19 infection has been documented to range from 7.0-41.3%.…”
Section: Introductionmentioning
confidence: 99%